Kecurangan Laporan Keuangan: Profitabilitas, Ukuran Perusahaan, Opportunity pada Perusahaan Sub Sektor Property dan Real Estate - Mega Andani; Indra Saputra; Hanifah Hanifah; Ahmad sulthon Nasyir (Pusat Riset dan Inovasi Nasional, 2024)
The purpose of this study is to analyze the effect of Profitability (X1), Company Size (X2), Opportunity (X3) on Financial Report Fraud in Property and Real Estate Sub-Sector Companies listed on the Indonesia Stock Exchange in 2019-2022.The research method used is quantitative. The population of the study was 70 Property and Real Estate Sub-Sector Companies listed on the Indonesia Stock Exchange in 2019-2022. The research sample used 14 companies based on purposive sampling. Profitability is proxied by Return On Asset, Company Size, Opportunity, Financial Report Fraud is proxied by Earning management. Regression analysis uses logistic regression.The results of the study indicate that profitability has no effect on financial statement fraud. The variables Company Size and Opportunity have a negative effect on financial statement fraud. In the Property and Real Estate Sub-Sector Companies listed on the Indonesia Stock Exchange in 2019-2022.